Validation of the Thai Version of the Chronic Pain Acceptance Questionnaire-8 (CPAQ-8T) in Chronic Pain Patients - Pasutharnchat K; Seangrung R; Lertmongkonaksorn P; Kamdeang S (Journal of Pain Research)
Koravee Pasutharnchat, Rattaphol Seangrung, Prateep Lertmongkonaksorn, Sirima Kamdeang Department of Anesthesiology, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Koravee Pasutharnchat, Department of Anesthesiology, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Rachathewi, Bangkok, 10400, Thailand, Tel +6622011523 ; +66814381248, Fax +6622011569, Email kpasuth@gmail.comPurpose: Chronic pain significantly affects patients’ quality of life, leading to the avoidance of activities that exacerbate their pain. Embracing pain acceptance and willingness is crucial to maintain patients’ functionality. This study aimed to translate and validate the Chronic Pain Acceptance Questionnaire-8 (CPAQ-8) into the Thai language and to facilitate the assessment of pain acceptance in Thai patients.Patients and Methods: The study involved the translation of the English CPAQ-8 into a Thai version, subsequently, referred to as the CPAQ-8T. The psychometric properties of the CPAQ-8T were examined. Study participants were administered a set of questionnaires, including the 100-mm Visual Analog Scale (VAS), CPAQ-8T, and the Barthel Index for Activities of Daily Living (ADL). Test-retest reliability was assessed by readministering the CPAQ-8T two weeks after the initial test. The validity and overall reliability of the CPAQ-8T were thoroughly assessed.Results: A total of 160 patients with chronic pain at pain clinic, Ramathibodi Hospital completed all the questionnaires. The mean CPAQ-8T score was 24.2 (SD = 7.26). The CPAQ-8T score exhibited the expected correlation with the Barthel Index for ADL but showed no significant correlation with the VAS score, indicating moderate convergent validity. The internal consistency and test-retest reliability findings support the validity and reliability of the CPAQ-8T.Conclusion: The translation and validation of the CPAQ-8 into the Thai language offers a reliable and valid instrument for assessing pain acceptance in Thai patients with chronic pain. The results suggested that the CPAQ-8T is a valuable tool for healthcare professionals and researchers working in the field of chronic pain management.Keywords: chronic pain acceptance questionnaire, CPAQ-8, validation, reliability, psychometric properties